A Multistage Mechanism for Managing Aggressive Flows In the Next Generation Internet - Diego Lanzi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2001)
In this note, we provide a multistage game form whichmay be used for managing aggressive flows which may cause network congestion or monopolisation. The mechanism here presented attains economic effciency, technical effciency and other desirable properties.
Keywords: 330